FORECAST OF ELECTRIC ENERGY CONSUMPTION IN SANGGAU REGENCY USING COMBNED METHODS - Junardi, Ignasius Ari (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2024)
Electrical energy is an essential need in this era that continues to increase in line with economic and population growth. This condition must of course be anticipated as early as possible so that the provision of electrical energy can be available in sufficient quantities, thus forecasting electrical energy demand is an anticipatory step to see the growth in electrical energy demand which is expected to grow rapidly in the following years. In conducting this research, the data used is in the form of electrical energy customer data, connected power and electrical energy consumption which is then calculated and compared the results between the DKL 3.2 model and the simple linear regression method. The total forecast results of the DKL 3.2 method in 2028 are 141,990 customers, 444,266,970.17 kWh, 232,100,915.26 VA, while the simple linear regression method is 159,850 customers, 302,867,395.10 kWh, 305,291,235 VA. The results of the calculation of projected electrical energy demand in Sanggau Regency in 2024-2028 continue to increase, in the DKL 3.2 model for the number of customers the average annual increase is 3.292%, connected power is 3.126% and for electrical energy consumption is 15.031%. Meanwhile, for the simple linear regression method for the number of customers the average annual increase is 5.680%, connected power is 8.529% and for electrical energy consumption is 6.615%. From the comparison of the two methods for the linear regression method, the calculation is more accurate than the DKL 3.2 model with the difference in error in the number of electrical energy customers by 2.388%, connected power by 5.722% and electrical energy consumption by 8.416%